MsDAD1 acts as a heat-induced “senescence brake” in alfalfa - Song, Yuguang; Guo, Xinying; Wang, Linyao; Zheng, Yingying; Li, Ting; Dong, Wei (Frontiers in Plant Science, 2025)
Heat stress severely limits the productivity of alfalfa (Medicago sativa L.). In this study, the defender against apoptotic death 1 (DAD1) gene, MsDAD1, was identified and functionally characterized as a key positive regulator of heat tolerance. The expression of MsDAD1 was specifically and strongly induced by heat stress, and phylogenetic analysis confirmed its high conservation across plant species. Ectopic overexpression of MsDAD1 in transgenic alfalfa significantly enhanced tolerance to heat stress. Compared to wild-type plants, MsDAD1-overexpressing lines (MsDAD1-OE) exhibited reduced leaf chlorosis and abscission, higher relative water content, lower electrolyte leakage, greater chlorophyll retention, and diminished accumulation of reactive oxygen species (H2O2, O2-) and malondialdehyde (MDA), suggesting improved membrane integrity and reduced oxidative damage. Transcriptome (RNA-seq) analysis and subsequent physiological validation indicated that MsDAD1 suppresses heat-induced accumulation of jasmonic acid (JA) and abscisic acid (ABA) by down-regulating key biosynthetic genes, LOX1 and NCED1. As a result, MsDAD1-OE plants displayed attenuated JA- and ABA-mediated leaf senescence under heat stress. Furthermore, MsDAD1 overexpression delayed heat-induced flowering, correlating with the repression of flowering-promoting genes such as FT and ELF4. Collectively, these findings demonstrate that MsDAD1 enhances alfalfa heat tolerance by mitigating oxidative stress, modulating JA and ABA biosynthesis to delay senescence, and altering flowering time under high-temperature conditions. MsDAD1 represents a promising genetic target for improving heat resilience in alfalfa.